Urgensi Kebijakan Sebagai Upaya Pencegahan Judi Online di Perguruan Tinggi Berdasarkan Konsep Maslahah - Ramadi, Bagus; Panjaitan, Budi Sastra; Harahap, Abdul Aziz (Syekh Ali Hasan Ahmad Addary State Islamic University, 2024)
Online gambling cases are found not only in the general public but also in the educational environment. Educational institutions have become a paradox between the advancement of knowledge, morals and behavior of some of their students. As a result, there needs to be action taken by the government to prevent similar incidents from occurring in other educational institutions. The government is considered urgent to use policy instruments to stop online gambling in educational institutions, especially in universities (campuses). This qualitative research uses normative research with a statue approach. Using the literature method (library research). The data of this research is analyzed qualitatively, namely secondary data in the form of theories, definitions and substance from various literatures, and laws and regulations, as well as primary data obtained from literature studies, then analyzed with relevant laws, theories and expert opinions to formulate the benefits. The results showed that the impact caused by this online gambling game is very significant, including a bad stimulus for the Higher Education environment, namely the lack of interest or motivation to study for students, worsening the economy such as debt and decreasing spiritual or religious observance. In addition, it affects psychologically due to defeat, impaired health and triggers acts of criminality such as stealing and cheating.